Effect of Fertigation on Growth and Yield of Turmeric Cv. Mydukur - Syed Sadarunnisa (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2010)
A field experiment was conducted at Horticultural Research Station, Anantharajupet, to study the effect of fertigation on growth and yield of turmeric to standardize the quantum of fertilizers to be given through fertigation for improving the productivity of turmeric. This experiment was carried out in a randomized block design with 4 replications. The treatments consisted of T1 (100% RDF through drip), T2 (75% RDF through drip), T3 (50 % RDF through drip), T4 (100 % RDF through soil and drip irrigation) and control (100 % RDF through soil and conventional irrigation). RDF, i.e., recommended dose of fertilizers comprised of 180 Kg N, 60 Kg P2 O5 and 120 Kg K2O ha-1. In the case of T1-T3, N and K alone was applied through drip, while, phosphorus was applied as basal dose. Data of three seasons showed that, there was significant difference between farmers' practice and fertigation treatments and it was observed that the treatment in which 100% fertilizers was applied through drip recorded the maximum plant height (99.36 cm), number of tillers per plant (3.41) and fresh rhizome yield (12.24 t acre-1) this was on par with the treatment in which 75% fertilizers were applied through drip. The B:C ratio was highest (1.49) in plants supplied with 75% RDF through drip. This shows that, fertigation with 75% RDF through drip in turmeric is profitable.